Expression of dihydropyrimidine dehydrogenase (DPD) and hENT1 predicts survival in pancreatic cancer - Elander, Nils O.; Neoptolemos, John P.; Büchler, Markus W. (British journal of cancer, 2018)
Dihydropyrimidine dehydrogenase (DPD) tumour expression may provide added value to human equilibrative nucleoside transporter-1 (hENT1) tumour expression in predicting survival following pyrimidine-based adjuvant chemotherapy. DPD and hENT1 immunohistochemistry and scoring was completed on tumour cores from 238 patients with pancreatic cancer in the ESPAC-3(v2) trial, randomised to either postoperative gemcitabine or 5-fluorouracil/folinic acid (5FU/FA). DPD tumour expression was associated with reduced overall survival (hazard ratio, HR = 1.73 [95% confidence interval, CI = 1.21-2.49], p = 0.003). This was significant in the 5FU/FA arm (HR = 2.07 [95% CI = 1.22-3.53], p = 0.007), but not in the gemcitabine arm (HR = 1.47 [0.91-3.37], p = 0.119). High hENT1 tumour expression was associated with increased survival in gemcitabine treated (HR = 0.56 [0.38-0.82], p = 0.003) but not in 5FU/FA treated patients (HR = 1.19 [0.80-1.78], p = 0.390). In patients with low hENT1 tumour expression, high DPD tumour expression was associated with a worse median [95% CI] survival in the 5FU/FA arm (9.7 [5.3-30.4] vs 29.2 [19.5-41.9] months, p = 0.002) but not in the gemcitabine arm (14.0 [9.1-15.7] vs. 18.0 [7.6-15.3] months, p = 1.000). The interaction of treatment arm and DPD expression was not significant (p = 0.303), but the interaction of treatment arm and hENT1 expression was (p = 0.009). DPD tumour expression was a negative prognostic biomarker. Together with tumour expression of hENT1, DPD tumour expression defined patient subgroups that might benefit from either postoperative 5FU/FA or gemcitabine.